2018
DOI: 10.1038/s41598-018-32400-7
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation enhances Zika virus infection of neuronal brain cells

Abstract: Zika virus (ZIKV) is an emerging, mosquito-borne pathogen associated with a widespread 2015–2016 epidemic in the Western Hemisphere and a proven cause of microcephaly and other fetal brain defects in infants born to infected mothers. ZIKV infections have been also linked to other neurological illnesses in infected adults and children, including Guillain-Barré syndrome (GBS), acute flaccid paralysis (AFP) and meningoencephalitis, but the viral pathophysiology behind those conditions remains poorly understood. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
(42 reference statements)
2
14
0
Order By: Relevance
“…These studies used different ZIKV strains, multiplicities of infection, and lengths of infection, and thus the extent of ZIKV infection ranged from 2.5% to 90% [27,[29][30][31][32][33][34][35]. Consistent with earlier reports of ZIKV infection in SH-SY5Y cells [80,81], immunofluorescence analyses revealed that 40% of cells were infected (Figure 1a,b). While we recognized that the differential gene expression and alternative splicing analyses collected would be on a modest number of infected cells, we reasoned that this level of infection would be comparable to the previous transcriptome-wide studies [27,[29][30][31][32][33][34][35] and that, thus, changes in the alternative splicing landscape would model such changes in ZIKV-infected neurons.…”
Section: Discussionsupporting
confidence: 86%
“…These studies used different ZIKV strains, multiplicities of infection, and lengths of infection, and thus the extent of ZIKV infection ranged from 2.5% to 90% [27,[29][30][31][32][33][34][35]. Consistent with earlier reports of ZIKV infection in SH-SY5Y cells [80,81], immunofluorescence analyses revealed that 40% of cells were infected (Figure 1a,b). While we recognized that the differential gene expression and alternative splicing analyses collected would be on a modest number of infected cells, we reasoned that this level of infection would be comparable to the previous transcriptome-wide studies [27,[29][30][31][32][33][34][35] and that, thus, changes in the alternative splicing landscape would model such changes in ZIKV-infected neurons.…”
Section: Discussionsupporting
confidence: 86%
“…The human neuroblastoma cell lines SH-SY5Y and BE(2)-M17 are two of the best-characterised cell lines for studies into human neurological disease, such as Alzheimer’s and Parkinson’s diseases (3035), and neurovirology (3946, 49, 52). Previous studies have confirmed their suitability as in vitro models of human neurons due to their expression of human neuron-specific markers, and the fact that their neuron-like phenotypes can be further improved through the use of chemical differentiation agents, such as RA and staurosporine (3638, 43).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from our lab and others have shown that ZIKV infects a variety of retinal (6, 12, 17, 2224), corneal (25), and other cell types, including neuronal cells (26, 27); placental cells (28, 29); skin fibroblasts, keratinocytes, and dendritic cells (30); and endometrial stromal cells (31). In vivo studies using local as well systemic infection in mouse models have demonstrated that ZIKV causes a variety of ocular pathologies and infects various parts of the eye including ciliary body, iris, conjunctiva, retina, and optic nerve head (6, 12, 17).…”
Section: Introductionmentioning
confidence: 94%